Counting in a disappearing land. The story of the research project that aims to establish links between people livestock and wildlife in the Kenyan Maasai Mara - International Livestock Research Institute (International Livestock Research Institute, 2007)
This Other comprises a 10 minutes film that narrates the story of the research project - the aim of which is to establish links between people livestock and wildlife in the Kenyan Maasai Mara. It is produced by ILRI and Colorado State University. The kenyan Maasai Mara is home to the Maasai people who herd their livestock across the open plains. These plains also sustain a wide variety of wildlife, as well as forming the venue for a huge yearly East African migration of Animals. Maasai, wildlife and livestock have lived together for centuries. However recent population growth, shrinking pastures and other resources, and changes in land laws means the Maasai might soon have to plant crops to survive. If that happens, it will be the end of wildlife - and the Maasai way of life. Dr. Robin Reid, a scientist from ILRI, leads a team of community members and researchers. Their project has taken them across the Mara plains, day and night, throughout the seasons and years, to count anything that moves there - wildlife, livestock, people, cars and even dogs. They want to find out more about the relationship between all the parts of this complex eco-system, so that they can make a difference - before it is too late.